Allies or Servants? The Journey of Indian Conquistadors in the Lienzo of Analco. - Yannakakis, Yanna (Ethnohistory)
This article analyzes ambiguities in the roles and identities of the indigenous allies of the Spanish conquerors of Oaxaca's Sierra Norte by putting into dialogue the Lienzo of Analco—an indigenous-produced cartographic narrative of the conquest of the sierra—and archival documentation. The Lienzo of Analco communicates the story of the conquest in an area far removed from pre-Hispanic Mesoamerican power centers from the perspective of lesser or "forgotten" allies of the Spanish conquerors: naborías (native people in the service of Spaniards, who were neither slave nor free); and it recounts the birth of their ethnic polity, the barrio of Analco. The status of these indigenous allies marks a central tension in the lienzo's message: were they allies (indios conquistadores) or servants (naborías)? Historical documents say both, but the coexistence of these statuses poses a conundrum, since in other parts of Mesoamerica, Indian allies of the Spanish endeavored to distance themselves from naborías. The patrons and painters of the lienzo sought to resolve this tension by casting the dependent servitude of naborfas as merit-worthy service to the Spanish crown with the goal of achieving special collective status and privileges as "Indian conquistadors."